2017
DOI: 10.1093/annweh/wxx019
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trend in Wood Dust Exposure During the Production of Wood Pellets

Abstract: Analysis of the temporal trend in soft wood production units revealed declines in exposure of 20.5% per annum. It is important that precautions are taken to protect workers from a hazardous exposure to wood dust at the premises as the SOEL of 2 mg m-3 at some occasions is still exceeded. Additional measurements of wood dust exposure should be carried out on a regular basis in wood pellet production units in Sweden as well in other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…This cross-sectional study comprised three groups of workers from three different industries: paper mills, wood pellet plants, and iron foundries. In total, we studied 213 workers (85, 72, and 56, respectively) 18–20 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This cross-sectional study comprised three groups of workers from three different industries: paper mills, wood pellet plants, and iron foundries. In total, we studied 213 workers (85, 72, and 56, respectively) 18–20 …”
Section: Methodsmentioning
confidence: 99%
“…Employees came from six Swedish wood pellets plants involved in industrial production of wood pellets 19 . The six plants had a similar production process, and two of the plants also produced briquettes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term annual trends of À11% in wood dust exposure concentrations were reported for different industries based on data in OSHA's Integrated Management Information System (1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997). A recent study from Sweden in the wood pellet production showed an even steeper decline of À20% per annum [48].…”
Section: Wood Dustmentioning
confidence: 98%
“…Long‐term annual trends of −11% in wood dust exposure concentrations were reported for different industries based on data in OSHA's Integrated Management Information System (1979–1997). A recent study from Sweden in the wood pellet production showed an even steeper decline of −20% per annum [48].…”
Section: Process‐generated Substancesmentioning
confidence: 99%